Daratumumab for the Management of Newly Diagnosed and Relapsed/Refractory Multiple Myeloma: Current and Emerging Treatments - Offidani, Massimo; Corvatta, Laura; Morè, Sonia; Nappi, Davide; Martinelli, Giovanni; Olivieri, Attilio; Cerchione, Claudio (Frontiers in Oncology, 2021)
Immunotherapy is changing the paradigm of MM management and daratumumab is the first-in-class human monoclonal antibody targeting CD38 approved for the treatment of this malignancy. Daratumumab exerts anti-myeloma activity by different mechanisms of action as antibody-dependent cellular cytotoxicity (ADCC), antibody-dependent cellular phagocytosis (ADCP), complement-dependent cytotoxicity (CDC), direct apoptosis and immunomodulation. After GEN501 and SIRIUS trials showed efficacy of daratumumab monotherapy in heavily pretreated RRMM, in patients with at least two previous line of therapy, two phase III trials demonstrated superior ORR and PFS using triplets daratumumab-bortezomib-desamethasone (DVd) vs Vd (CASTOR) or daratumumab-lenalidomide-dexamethasone (DRd) vs Rd (POLLUX) in relapsed-refractory MM patients; so these combinations have been approved and introduced in clinical practice. The ongoing phase III CANDOR is evaluating the triplet daratumumab-carfilzomib-dexamethasone (DKd) vs Kd whereas phase III APOLLO trial is exploring daratumumab-pomalidomide-dexamethasone (DPd) vs PD. Many other trials exploring daratumumab combinations in relapsed-refractory MM are ongoing and they will provide other interesting results. In newly diagnosed tranplant-eligible patients, phase III CASSIOPEIA trial found the combination daratumumab-bortezomib-thalidomide-dexamethasone (Dara-VTd) significantly to improve sCR rate and PFS compared with VTD whereas in the phase II GRIFFIN study, comparing daratumumab-bortezomib-lenalidomide-dexamethasone (Dara-VRD) vs VRD, sCR rate was significantly higher using quadruplet combination. Many studies are evaluating daratumumab in consolidation and maintenance therapy after ASCT. As regard patients ineligible for ASCT, a great efficacy of daratumumab-containing combinations was reported by the phase III trials ALCYONE and MAIA, exploring daratumumab-bortezomib- melphalan-prednisone (DVMP) vs VMP and daratumumab- lenalidomide-dexamethasone (DRd) vs Rd, respectively. These studies provided results never seen before in this setting. The aim of this paper is to critically review the results obtained with regimens containing daratumumab both in relapsed-refractory and in newly diagnosed MM.